2017
DOI: 10.1016/j.envpol.2017.08.026
|View full text |Cite
|
Sign up to set email alerts
|

Microplastic pollution identified in deep-sea water and ingested by benthic invertebrates in the Rockall Trough, North Atlantic Ocean

Abstract: Microplastics are widespread in the natural environment and present numerous ecological threats. While the ultimate fate of marine microplastics are not well known, it is hypothesized that the deep sea is the final sink for this anthropogenic contaminant. This study provides a quantification and characterisation of microplastic pollution ingested by benthic macroinvertebrates with different feeding modes (Ophiomusium lymani, Hymenaster pellucidus and Colus jeffreysianus) and in adjacent deep water > 2200 m, in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
153
1
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 359 publications
(181 citation statements)
references
References 61 publications
10
153
1
1
Order By: Relevance
“…Many potential microplastic fibres from the FT-IR subsample in this study were identified with high spectral matches as cellulose-based particles, despite their appearance under visual examination as microplastics. Indeed, this has begun to be reported elsewhere within the literature (Cai et al, 2017;Courtene-Jones, Quinn, Gary, Mogg, & Narayanaswamy, 2017;Remy et al, 2015). For example, blue cotton indigo fibres from samples of waste water treatments plants can show close visual similarity to polyacrylic fibres (Dyachenko, Mitchell, & Arsem, 2017;Silva et al, 2018).…”
Section: Microplastic Polymer Identificationmentioning
confidence: 74%
“…Many potential microplastic fibres from the FT-IR subsample in this study were identified with high spectral matches as cellulose-based particles, despite their appearance under visual examination as microplastics. Indeed, this has begun to be reported elsewhere within the literature (Cai et al, 2017;Courtene-Jones, Quinn, Gary, Mogg, & Narayanaswamy, 2017;Remy et al, 2015). For example, blue cotton indigo fibres from samples of waste water treatments plants can show close visual similarity to polyacrylic fibres (Dyachenko, Mitchell, & Arsem, 2017;Silva et al, 2018).…”
Section: Microplastic Polymer Identificationmentioning
confidence: 74%
“…The presence of microplastic at different levels of the aquatic trophic web was documented by the literature [18]; D'Alessandro et al [19] reported relationships among the plastic litter, chemical pollutants and observed benthic biodiversity. Microplastic is recorded in edible seafood and mariculture products [20,21] such as pelagic fish species [22], benthic species [15,23], bivalves [24][25][26], holothurians [27], and marine mammals [28] as wider documented by the recent literature [29], and citations therein. However, at this time, there are no specific regulations in Europe [30].…”
Section: Introductionmentioning
confidence: 97%
“…Recently Frias and Nash [6] defined microplastics as "any synthetic solid particle or polymeric matrix, with regular or irregular shape and with size ranging from 1 µm to 5 mm, of either primary or secondary manufacturing origin, which are insoluble in water". To date microplastics have been detected in water [7,8], and sediments [9] coming from different environments worldwide: sea surface and water column [10], lakes and rivers [4,11], coastal areas [12], harbours [13], marine protected areas [14], deep oceans [15], polar ecosystems [16], and coral reefs [17].…”
Section: Introductionmentioning
confidence: 99%
“…Benthos is an important feeding environment for many marine species (Anderson and Lovvorn, 2008;MacDonald et al, 2012;Gittman and Keller, 2013) and a recent study has shown marine benthic species ingest microplastics (Courtene-Jones et al, 2017). Knowledge of the harmful effects of microplastics on benthic marine species and communities is growing (Green, 2016;Galloway et al, 2017), however, little is known of past microplastic accumulation in benthic environments.…”
Section: Introductionmentioning
confidence: 99%